Being 'nice' or being 'normal': girls resisting discourses of 'coolness'. Issue 3 (3rd May 2016) - Paechter, Carrie; Clark, Sheryl
Abstract : In this paper we consider discourses of friendship and belonging mobilised by girls who are not part of the dominant 'cool' group in one English primary school. We explore how, by investing in alternative and, at times, resistant, discourses of 'being nice' and 'being normal' these 'non-cool' girls were able to avoid some of the struggles for dominance and related bullying and exclusion found by us and other researchers to be a feature of 'cool girls' groupings. We argue that there are multiple dynamics in girls' lives in which being 'cool' is only sometimes a dominant concern. There are some children for whom explicitly positioning themselves outside of the 'cool' group is both resistant and protective, providing a counter-discourse to the dominance of 'coolness'. In this paper, which is based on observational and interview data in one school in the south of England, we focus on two main groupings of intermediate and lower status girls, as well as on one 'wannabe' 'cool girl'. While belonging to a lower status group can bring disadvantages for the girls we studied, there were also benefits.